2013
DOI: 10.2174/22103031113039990017
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte biology and space flight

Abstract: The last decade has seen an impressive expansion of our understanding of the role of osteocytes in skeletal homeostasis. These amazing cells, deeply embedded into the mineralized matrix, are the key regulators of bone homeostasis and skeletal mechano sensation and transduction. They are the cells that can sense the mechanical forces applied to the bone and then translate these forces into biological responses. They are also ideally positioned to detect and respond to hormonal stimuli and to coordinate the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This hypoxia-induced self-assembly of the endosteum-like layer is particularly noteworthy, as it has not been observed in any other culture system reported to date. [30][31][32]37,38 Second, hypoxia significantly enhanced the gene expressions of SOST and FGF23, while decreasing that of ALPL. Taking culture conditions separately, replacing traditional normoxic 2D cultures with hypoxia significantly increased SOST expression by fourfold, while introducing the 3D configuration to the traditional 2D normoxic cultures significantly increased SOST by twofold (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…This hypoxia-induced self-assembly of the endosteum-like layer is particularly noteworthy, as it has not been observed in any other culture system reported to date. [30][31][32]37,38 Second, hypoxia significantly enhanced the gene expressions of SOST and FGF23, while decreasing that of ALPL. Taking culture conditions separately, replacing traditional normoxic 2D cultures with hypoxia significantly increased SOST expression by fourfold, while introducing the 3D configuration to the traditional 2D normoxic cultures significantly increased SOST by twofold (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In the past, this mechanotransduction function could not be equivocally replicated in vitro due to: (1) the relatively insufficient SOST and FGF23 expressions of osteocytic cell lines 2226 and (2) the difficulty of maintaining the phenotype of primary osteocytes due to their osteoblastic dedifferentiation and proliferation during 2D culture. 27,28 Also, state-of-the-art 3D bone tissue models, developed by other investigators, 29–32 cannot replicate physiologically relevant cell-to-cell distance and strong expressions of SOST and FGF23 as the key markers of mature osteocytes. Note that FGF23 is a hormone expressed by osteocytes to regulate phosphate homeostasis, and is gaining importance since it has been recently implicated to facilitate prostate cancer progression 33 and to be elevated in multiple myeloma patients.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of RANKL on osteoclasts is inhibited by osteoprotegerin (OPG), a decoy receptor produced in stromal cells. Mammalian sclerostin suppresses OPG production by inhibiting Wnt signaling in stromal cells, thus facilitating osteoclastogenesis (Kubota et al 2009;Silva and Branco 2011;Pajevic et al 2013;Delgado-Calle et al 2017). Several groups, including ours, have reported that fish scales are morphologically and functionally similar to mammalian bones in some ways.…”
Section: Methodsmentioning
confidence: 74%
“…It has been reported that both Sost −/− and osteocyte-ablated mice showed resistance to bone loss induced by hindlimb unloading via tail suspension (Tatsumi et al 2007;Lin et al 2009). These previous studies have provided evidence that sclerostin produced by osteocyte has an important role in the response of mechanical stimuli (Pajevic et al 2013;Delgado-Calle et al 2017;Hinton et al 2018).…”
Section: Methodsmentioning
confidence: 94%